Supply Chain Systems Utilization towards the Global Economy in Special Economic Zones Perspective - Sutiarnoto, Sutiarnoto; Leviza, Jelly; Arif, Arif; Devi Azwar, T.Keizerina (ExcelingTech, 2020)
Abstract— The core of the Special Economic Zone is an effort to increase investment by developing certain regions/zones to spur economic growth. Through examples from the Middle East and South Asia I explain how the objectives of excellence in business performance and quality management have been attained without substantive investment by following the basic principles and concepts of Supply Chain Management and Quality Management. The effort to realize Special Economic Zones as an effort to increase investment in Indonesia is a choice now. Although these efforts may not be separated from the constraints faced with regard to services, facilities, and infrastructure as well as possible obstacles related to the response of investors in the framework of the realization of the Special Economic Zones. However, such efforts will accumulate capital with rapid growth or achieve social progress. This is in line with the tendency of the global economy to continue, which in turn makes economic activity between countries increase and also increasing foster regional economic activity.